Racial/ethnic disparities in opioid overdose prevention: comparison of the naloxone care cascade in White, Latinx, and Black people who use opioids in New York City - Maria R. Khan; Lee Hoff; Luther Elliott; Joy D. Scheidell; John R. Pamplin; Tarlise N. Townsend; Natalia M. Irvine; Alex S. Bennett (BMC, 2023)
Abstract Background Drug overdose mortality is rising precipitously among Black people who use drugs. In NYC, the overdose mortality rate is now highest in Black (38.2 per 100,000) followed by the Latinx (33.6 per 100,000) and white (32.7 per 100,000) residents. Improved understanding of access to harm reduction including naloxone across racial/ethnic groups is warranted. Methods Using data from an ongoing study of people who use illicit opioids in NYC (N = 575), we quantified racial/ethnic differences in the naloxone care cascade. Results We observed gaps across the cascade overall in the cohort, including in naloxone training (66%), current possession (53%) daily access during using and non-using days (21%), 100% access during opioid use (20%), and complete protection (having naloxone and someone who could administer it present during 100% of opioid use events; 12%). Naloxone coverage was greater in white (training: 79%, possession: 62%, daily access: 33%, access during use: 27%, and complete protection: 13%, respectively) and Latinx (training: 67%, possession: 54%, daily access: 22%, access during use: 24%, and complete protection: 16%, respectively) versus Black (training: 59%, possession: 48%, daily access:13%, access during use: 12%, and complete protection: 8%, respectively) participants. Black participants, versus white participants, had disproportionately low odds of naloxone training (OR 0.40, 95% CI 0.22-0.72). Among participants aged 51 years or older, Black race (versus white, the referent) was strongly associated with lower levels of being trained in naloxone use (OR 0.20, 95% CI 0.07-0.63) and having 100% naloxone access during use (OR 0.34, 95% CI 0.13-0.91). Compared to white women, Black women had 0.27 times the odds of being trained in naloxone use (95% CI 0.10-0.72). Conclusions There is insufficient protection by naloxone during opioid use, with disproportionately low access among Black people who use drugs, and a heightened disparity among older Black people and Black women.